Effects of vitamins C and E on semen quality and reproductive hormones in yellow mystus (Hemibagrus spilopterus) - Sommuek, Natthawan; Kasamawut, Krittima; Ngamsnae, Praneet; Sreeputhorn, Kosit; Saowakoon, Samnao (Agriculture and Natural Resources, 2023)
Importance of the work: Breeding success depends partly on sperm quality which could be enhanced by vitamin supplementation in feed. Objectives: To investigate the effects of vitamins C and E and their combination on semen quality and sex hormones in yellow mystus. Materials & Methods: Male yellow mystus aged 1 yr were stocked in three cages (each 4 m2) and fed with 32% protein commercial feed supplemented with: 1) no vitamins as the control; 2) vitamin C (Vit C) at 1,000 mg/kg; 3) vitamin E (Vit E) at 500 mg/kg; 4) Vit C at 1,000 mg/kg + Vit E at 500 mg/kg. In each experimental group, the growth, semen quality and sex hormones were investigated. Results: The results showed that vitamin supplementation did not affect the growth of yellow mystus. On day 30, the Vit C, Vit E and Vit C + Vit E groups had higher gonadosomatic index values than the control (p < 0.05). On days 30 and 60, the Vit C + Vit E group had the highest mean sperm motility (87.33 ± 3.05%; p < 0.05). On day 30, the Vit C and the Vit C + Vit E groups had higher sperm viability than the control (p < 0.05), while on day 60, the Vit C, Vit E, and Vit C + Vit E groups had higher sperm viability (p < 0.05). In addition, the Vit C + Vit E group had significantly higher testosterone levels compared to the control and the Vit C group measured on day 60. Main finding: Adding Vit C + Vit E in the diet enhanced the semen quality and sex hormones of yellow mystus. This approach could serve as an effective method to increase the fingerling production of yellow mystus.